Seroprevalence of bovine viral diarrhoea in dairy herds of the Mantaro Valley, Junín Region, Peru - Arauco Villar, Fernando (2018)
The seroprevalence of bovine viral diarrhoea (DVB) in dairy herds and the presence of persistently infected animals in the four provinces of the Mantaro Valley, Peru were determined using the ELISA technique. A total of 425 blood samples were taken from animals of 37 herds and an epizootic survey was applied in parallel. The prevalence of DVB of the four provinces was 66.3% and the prevalence/herd of 64.8%. The province of Concepción showed the highest sample and herd prevalence (75.2 and 75.5%, respectively, and Huancayo had the lowest (48.3 and 52.3%, respectively). The prevalence of PI animals with DVB in the four provinces was 5.8%. Risk factors for the presentation of DVB were the intensive breeding system (OR: 6.545), open herd type (OR: 6.33), use of artificial insemination (OR: 7.895) and massive presence of rats (OR: 5.714). There was a positive association between high prevalence of DVB with the presence of repeat breeder cows, abortions and anomalous births.